Post-Mastectomy Surgical Pocket Irrigation With Triple Antibiotic Solution vs Chlorhexidine Gluconate: A Randomized Controlled Trial Assessing Surgical Site Infections in Immediate Tissue Expander Breast Reconstruction. (22nd July 2021) - Nguyen, Lyly; Afshari, Ashkan; Green, Japjit; Joseph, Jeremy; Yao, Jun; Perdikis, Galen; Higdon, Kent K
Abstract: Background: Post-mastectomy pocket irrigation solution choice is debated and primarily surgeon dependent. We compare triple antibiotic solution (TAS) with 0.05% chlorhexidine gluconate (CHG). Objectives: The purpose of this study was to determine surgical site infection (SSI) rates after utilizing TAS vs CHG for breast pocket irrigation in immediate tissue expander (TE) breast reconstruction. Methods: A prospective, blinded, randomized controlled trial was performed in patients (18-81 years old) who underwent bilateral mastectomy with TE reconstruction. In each patient, 1 mastectomy pocket was randomized to TAS and the other to CHG. Both the TE and the pocket were irrigated in the respective solution. The primary outcome was the incidence of SSI. Secondary outcomes were rates of mastectomy flap necrosis, hematoma, and seroma. Results: A total of 88 patients who underwent bilateral immediate breast reconstruction were enrolled. Demographic and operative characteristics were equivalent because each patient served as their own control. Between the TAS and CHG groups, the incidence of SSI did not differ (5 [4.5%] vs 7 [8.0%], P  = 0.35), including minor infections (2 [2.3%] vs 1 [1.1%], P  = 0.56), major infections (2 [2.3%] vs 6 [6.8%], P  = 0.15), and those resulting in explantation (2 [2.3%] vs 5 [4.5%], P  = 0.25). Necrosis, hematoma, or seroma formation also did not differ. No patients who developed SSI received radiation. Conclusions: This study does not demonstrate a statistically significant difference in SSI between TAS and CHG irrigation, though TAS approached statistical significance for lower rates of infectious complications. Level of Evidence: 2: